2017
DOI: 10.1186/s12870-017-1112-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of wheat calcium ATPases and potential role of selected ACAs and ECAs in calcium stress

Abstract: BackgroundP2- type calcium ATPases (ACAs-auto inhibited calcium ATPases and ECAs-endoplasmic reticulum calcium ATPases) belong to the P- type ATPase family of active membrane transporters and are significantly involved in maintaining accurate levels of Ca2+, Mn2+ and Zn2+ in the cytosol as well as playing a very important role in stress signaling, stomatal opening and closing and pollen tube growth. Here we report the identification and possible role of some of these ATPases from wheat.ResultsIn this study, AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
3
11
0
Order By: Relevance
“…In the current study, we aimed genome-wide identification, characterization, expression profiling, and co-expression analyses of type II Ca 2+ ATPases in various tissue developmental stages and in the presence of numerous stresses in T. aestivum . During the compilation of our findings, we found that Aslam et al, (2017) [ 23 ] have also identified Ca 2+ ATPases in T. aestivum . However, they had not performed inclusive characterization of complete gene family.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the current study, we aimed genome-wide identification, characterization, expression profiling, and co-expression analyses of type II Ca 2+ ATPases in various tissue developmental stages and in the presence of numerous stresses in T. aestivum . During the compilation of our findings, we found that Aslam et al, (2017) [ 23 ] have also identified Ca 2+ ATPases in T. aestivum . However, they had not performed inclusive characterization of complete gene family.…”
Section: Introductionsupporting
confidence: 74%
“…Further, two (LOC_Os02g08010 and LOC_Os08g40530) out of 12 rice ACA proteins also lacked CaATP_NAI domain [ 10 ] as observed in case of TaACA2 and TaACA6. Aslam et al, (2017) [ 23 ] identified only 27 TaACA proteins; they had not reported TaACA4 genes. Furthermore, we identified a total of 14 (11 TuACAs and 3 TuECAs) and 15 (12 AeACAs and 3 AeECAs) type II Ca 2+ ATPase proteins in the T. urartu and Ae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aestivum as compared to O . sativa [ 44 ]. It has all the attributes of a model plant such as small genome size (~355MBp), self-fertility, short life cycle (8–11 weeks), simple growth conditions, and easily manipulatable genome.…”
Section: Discussionmentioning
confidence: 99%
“…; Aslam et al . ). This statement might explain why increasing the Ca supplementation in the soil does not increase the Ca concentration in rice shoots and grains in a long‐term application However, increasing the Ca acetate amount might induce expression of ACA , especially ACA3 and ACA13 , to improve rice development under Cd stress.…”
Section: Resultsmentioning
confidence: 99%